2009
DOI: 10.1098/rstb.2009.0100
|View full text |Cite
|
Sign up to set email alerts
|

Options for control of foot-and-mouth disease: knowledge, capability and policy

Abstract: Foot-and-mouth disease can be controlled by zoo-sanitary measures and vaccination but this is difficult owing to the existence of multiple serotypes of the causative virus, multiple host species including wildlife and extreme contagiousness. Although intolerable to modern high-production livestock systems, the disease is not usually fatal and often not a priority for control in many developing countries, which remain reservoirs for viral dissemination. Phylogenetic analysis of the viruses circulating worldwide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
186
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(197 citation statements)
references
References 54 publications
3
186
0
1
Order By: Relevance
“…FMD is not a fatal disease in livestock but results in substantive production losses following recovery. Because it is not fatal, many low-income countries do not prioritise FMD control [27]. The negative bystander effects of FMD control as seen in Cumbria (NW England) would not have occurred, but for the mass slaughter of animals and the severe movement restrictions in the countryside that the FMD control policy entailed.…”
Section: Glossarymentioning
confidence: 99%
“…FMD is not a fatal disease in livestock but results in substantive production losses following recovery. Because it is not fatal, many low-income countries do not prioritise FMD control [27]. The negative bystander effects of FMD control as seen in Cumbria (NW England) would not have occurred, but for the mass slaughter of animals and the severe movement restrictions in the countryside that the FMD control policy entailed.…”
Section: Glossarymentioning
confidence: 99%
“…In southern Africa, 3 main FMD virus serotypes are frequently detected: SAT1, SAT2 and SAT3 (Southern African Territories) (Rweyemamu et al 2008, Paton et al 2009), among which no cross-immunity has been observed. The three SATs circulate in domestic and wild populations.…”
Section: Introductionmentioning
confidence: 99%
“…This disease is due to an aphthovirus that can infect ungulates and is highly contagious with a basic reproductive number varying from 2 to 38 depending on climatic conditions (Haydon et al 1997). FMD has important economic impacts and constrains beef exporting countries to implement massive control programs (e.g., through culling, zoning and/or vaccination) (Paton et al 2009). Although FMD is widespread worldwide, only 7 serotypes of the virus have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…This highly contagious disease is harbored by different hosts and exists as seven different serotypes (O, A, C, Southern African Territories [SAT] 1, SAT 2, SAT 3 and Asia 1), which are not uniformly distributed across the world (Di Nardo et al, 2011;Brito et al, 2016). The FMD virus infection is maintained within three continental epidemiological clusters in Africa, Asia and South America (Paton et al, 2009). FMD affects economies directly by reducing animal production (Wekesa et al, 2015;FAO/OIE, 2014).…”
Section: Introductionmentioning
confidence: 99%